Computation of characteristics of electronegative metamaterial in circular waveguide based on multilayered dielectric - Калиберда, М.Е.; Погарский, С.А.; Дроздов, К.С. (Radiotekhnika, 2012)
The multilayered structure, where every layer corresponds to dielectric disc in a circular waveguide, is considered. The system is excited by the ТЕ11 mode. The operator method is applied for analysis. The determination of optimal dependence of relative dielectric permittivity of a single layer versus frequency, at which the dielectric with negative dielectric permittivity corresponds to our multilayered structure, is performed.